Promoting female economic inclusion for tax performance in Sub-Saharan Africa - Simplice Asongu; Alex Adegboye; Joseph Nnanna (African Governance and Development Institute (AGDI), 2020)
This study explores whether female economic inclusion enhances tax performance in a sample of 48 countries in Sub-Saharan Africa from 2000 to 2018. The study's empirical evidence is based on the generalized method of moments in order to account for endogeneity concerns. Three tax performance measurements are used, notably, total taxes revenue excluding social contributions, reported tax revenue derived from natural resources sources, and total non-resource tax revenue. Three female inclusion indicators are used, namely, female employment in industry, female labour force participation, and female employment. The following empirical evidences are documented; (i) There is a negative net effect from the enhancement of female employment in the industry on the total tax revenue. (ii) There is a positive net effect of female employment in the industry on the non-resource taxes. An extended threshold analysis is performed to establish the critical masses that could further influence tax performance positively. The following thresholds are established. (i) a minimum of 15.35 "employment in industry, female (% of female employment)" for the total tax revenue and (ii) a maximum of 23.75 "employment in industry, female (% of female employment)" for the non-resource tax revenue. These critical masses are crucial for sustainable development because, below or beyond these thresholds, policy makers should complement the female economic inclusion with other economic measures designed to improve tax performance in Sub-Saharan Africa.
Keywords: H20; H71; I28; J08; J21; 330; Gender; economic inclusion; tax performance; sustainable development; Africa